STUDI PENGARUH STATUS PERKAWINAN DAN PEKERJAAN PADA PASIEN TUBERKULOSIS DI RUMAH SAKIT DKT PURWOKERTO - Peppy Octaviani (Universitas Harapan Bangsa Purwokerto, 2018)
ABSTRACT Pulmonary tuberculosis (TB) is a contagious pulmonary infectious disease that is still a health problem in the world, especially developing countries. Tuberculosis has been proclaimed by WHO (World Health Organization) as Global Emergency since 1992. The purpose of this study is to find out what physical characteristics are at risk of tuberculosis in DKT Hospital Purwokerto. The research design used in this study was a descriptive study with a cross-sectional approach to determine the characteristics of pulmonary TB patients who were adherent to treatment and those who did not comply with treatment at the DKT Hospital in Purwokerto. This research was conducted at the DKT Purwokerto Hospital in May 2018. The samples studied in this study were pulmonary TB patients who were obedient to treatment and non-compliance with treatment at the DKT Purwokerto Hospital for the period of 1 January - 30 December 2017 that met the sample criteria. The results of the study have no relationship between age and the results of sputum examination at the Purwokerto DKT Hospital (p value = 0.286), there is no relationship between sex with the results of sputum examination at DKT Purwokerto Hospital (p value = 0.261). Keywords: Pulmonary TBC, Characteristics, Phlegm Examination